Strong Linkage Between Precipitation Intensity and Monsoon Season Groundwater Recharge in India. Issue 11 (12th June 2018) - Asoka, Akarsh; Wada, Yoshihide; Fishman, Ram; Mishra, Vimal
Abstract: Groundwater is a lifeline for millions of people in India, which is affected by the year‐to‐year variability of precipitation amount and characteristics (low and high intensity). Precipitation intensity has been observed and projected to change in India. However, the crucial impact of precipitation intensity on groundwater recharge in India remains unknown. Here we use in situ data from more than 5, 800 groundwater wells to show that precipitation intensity is strongly linked with groundwater recharge in India. In the northwest and north central India, the monsoon season groundwater recharge is linked with the low‐intensity precipitation, while in South India high‐intensity precipitation is a major driver of groundwater recharge. Observed long‐term changes in precipitation characteristics show a decline in the low‐intensity rain in the northwest and north central India that are strongly driven by sea surface temperature over the Pacific Ocean. Increases in the high‐intensity precipitation in South India are linked with the sea surface temperatures in the Atlantic Ocean. Our results highlight the importance of precipitation intensity for the monsoon season groundwater recharge in India, which can provide insights to sustainably manage rapidly declining groundwater resources in India. Plain Language Summary: Sustainable management of groundwater resources in India is vital for ensuring food and water security for millions of people. Groundwater storage in India has declined due to excessive pumping for irrigation and decreased summer monsoon rainfall. There are efforts to enhance the groundwater recharge in India. However, the role of precipitation intensity for groundwater recharge remains unclear. We provide the first ever assessment of the linkage between groundwater recharge and precipitation intensity in India using observed data from more than 5, 800 wells. We show that low‐intensity precipitation is vital for groundwater recharge in the heavily irrigated North India. In South India, high‐intensity rainfall is a major driver of groundwater recharge in comparison to low‐intensity precipitation. Our findings can provide insights for management of groundwater recharge in India. Key Points: Low‐intensity rainfall is a major driver of groundwater recharge in India Low‐intensity rainfall controls groundwater recharge in north central and northwest India SST in Pacific and Atlantic Oceans controls the year‐to‐year variability in low‐ and high‐intensity rainfall in India